Mastering CSS for Web Developers (Smashing Media GmbH, 2011)
Are you stumped by the rather sophisticated nature of CSS? Getting a grip on this still dewy technology isn’t quite as hard as you might think. Connecting the dots is easier when you have all the vital facts within reach. And that's what “Mastering CSS” is all about. This eBook offers 15 hand-picked articles that overflow with professional advice and that reflect the deep experience of the Smashing Magazine authors you trust — authors who know exactly what they’re writing about.